Dude, you're a fag: masculinity and sexuality in high school : with a new preface - Pascoe, C. J. (University of California Press, 2012)
"High school and the difficult terrain of sexuality and gender identity are brilliantly explored in this smart, incisive ethnography. Based on eighteen months of fieldwork in a racially diverse working-class high school, Dude, You're a Fag sheds new light on masculinity both as a field of meaning and as a set of social practices. C.J. Pascoe's unorthodox approach analyzes masculinity as not only a gendered process but also a sexual one. She demonstrates how the 'specter of the fag' becomes a disciplinary mechanism for regulating heterosexual as well as homosexual boys and how the 'fag discourse' is as much tied to gender as it is to sexuality"–Provided by publisher.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; adolescents*; amériques; approches et analyses; californie; cours; discipline; ethnographie; hétérosexisme; masculinité; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Women's Barracks: The original 1950 tale of life and love in the free french army - Torres, Tereska; Mayne, Judith (The Feminist Press at CUNY, 2012)
This novel—based on the author's real-life experiences—is credited as the first candidly lesbian novel, originally published in 1950, that “scandalized mid-century America” (The New York Times).As the Blitz rains down over London, taboos are broken, affairs start and stop, and hearts are won and lost. This account of life among female Free French soldiers in a London barracks during World War II sold four million copies in the United States alone and many more worldwide. Women’s Barracks was banned for obscenity in several states and denounced by the House Select Committee on Current Pornographic Materials in 1952 as an example of how the paperback industry was “promoting moral degeneracy.” In spite of such efforts—or perhaps, in part, because of them—the novel became a record-breaking bestseller and inspired a whole new genre: lesbian pulp.Femmes Fatales restores to print the best of women’s writing in the classic pulp genres of the mid-20th century. From mystery to hard-boiled noir to taboo lesbian romance, these rediscovered queens of pulp offer subversive perspectives on a turbulent era.
Keywords: 1900-1999; 1940-1949; amour interdit; approches et analyses; europe; hétérosexisme; identités LGBTQIA2+; littérature; patriarcat; personnes lesbiennes; pulp lesbien; périodes historiques; royaume-uni; régions géographiques; sexualité; systèmes d'oppressions; thématiques